Pharmacogenomic Study Reveals New Variants of Drug Metabolizing Enzyme and Transporter Genes Associated with Steady-State Plasma Concentrations of Risperidone and 9-Hydroxyrisperidone in Thai Autism Spectrum Disorder Patients - Medhasi, Sadeep; Pinthong, Darawan; Pasomsub, Ekawat; Vanwong, Natchaya; Ngamsamut, Nattawat; Puangpetch, Apichaya; Chamnanphon, Monpat; Hongkaew, Yaowaluck; Pratoomwun, Jirawat; Limsila, Penkhae; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2016)
The present study sought to investigate the genetic variants in drug metabolizing enzyme and transporter (DMET) genes associated with steady-state plasma concentrations of risperidone among Thai autism spectrum disorder (ASD) patients. ASD patients taking risperidone for at least 1 month were enrolled for this pharmacogenomic study. Genotyping profile was obtained using Affymetrix DMET Plus array interrogating 1931 variants in 231 genes. Steady-state plasma risperidone and 9-hydroxyrisperidone were measured using liquid chromatography/tandem mass spectrometry assay. The final analysis included 483 markers for 167 genes. Six variants, ABCB11 (c.3084A > G, c.∗420A > G, c.∗368G > A, and c.∗236G > A) and ADH7 (c.690G > A and c.-5360G > A), were found to be associated with plasma concentrations of risperidone. 9-Hydroxyrisperidone and the total active-moiety levels were associated with six gene variants, SCLO1B1 (c.-11187G > A and c.521T > C), SLCO1B3 (c.334G > T, c.699A > G, and c.1557G > A), and SLC7A5 c.∗438C > G. Polymorphisms in UGT2B4 c.∗448A > G and CYP2D6 (c.1661G > C, c.4180G > C, and c.-2178G > A) showed considerable but not significant associations with metabolic ratio. This pharmacogenomic study identifies new genetic variants of DMET genes in monitoring risperidone therapy.